Caracterização micológica de méis roraimenses como critério de segurança alimentar - Simas, Eliane dos Santos (2015)
Some fungi are pathogenic, opportunistic and responsible for diseases in humans through food contaminated by the presence of mycotoxins. The present work aims to mycologically characterize samples of honey produced in Roraima, aiming at the food safety of this food. Analyzes of honeys from the experimental apiary of the Federal University of Roraima/UFRR, apiaries of Mucajaí and Cantá and of a commercial brand were carried out, collected in the rainy and dry seasons, making a total of eight samples. Filamentous fungi and yeasts were isolated and colony-forming units (CFU) were quantified to comply with Mercosur legislation. The conventional method of identification was based on characteristics of macro and micromorphology, and the molecular method, on PCR of rDNA and amplification of the ITS1-5.8S-ITS2 region with the universal primers ITS1 and ITS4. Of the analyzed samples, only the one collected in the Mucajaí apiary in the rainy season was considered unsuitable due to the amount of filamentous fungi and/or yeasts that exceeded 100 CFU. 63 CFU of filamentous fungi were obtained from samples of honey from Roraima, which were grouped into 19 morphotypes belonging to the genera Penicillium; Paecilomyces, Syncephalastrum, Humicola, Cladosporium, Eurotium and Monodictys, and the species Eurotium amstelodami, E. rubrum, Paecilomyces formosus, Penicillium citreonigrum, P. hispanicum, Syncephalastrum racemosum, Talaromyces mineoluteum and T. phialosporus. All genera isolated are potentially toxigenic, with the exception of Syncephalastrum. The mycological parameters observed in the samples reinforce the need for quality control of honey in the region, as well as the implementation of Good Manufacturing Practices.